Levitated Plasmonic Nanoantennas in an Aqueous Environment - Tuan, Yazgan; Kim, Ji Tae; Liu, Hsuan-Wei; Sandoghdar, Vahid (ACS nano, 2017)
We report on the manipulation of a plasmonic nanoantenna in an aqueous solution using an electrostatic trap created between a glass nanopipette and a substrate. By scanning a trapped gold nanosphere in the near field of a single colloidal quantum dot embedded under the substrate surface, we demonstrate about 8-fold fluorescence enhancement over a lateral full width at half-maximum of about 45 nm. We analyze our results with the predictions of numerical electromagnetic simulations under consideration of the electrostatic free energy in the trap. Our approach could find applications in a number of experiments, where plasmonic effects are employed at liquid-solid interfaces.
CRIS-Team Scopus Importer:2023-03-27
Keywords: electrostatic trapping; fluorescence enhancement; plasmofluidics; plasmonics; quantum dot